The architectural sense in the work of Hélio Oiticica - Neiva, Simone; Neves, Alexandre Emerick (Farol, 2025)
The article aims to study the architectural sense in the work of Hélio Oiticica, with the aim of understanding it in about ten of his works. The intention is to contribute to the expansion of the theoretical and critical architectural repertoire on the dialogue between art and architecture. In the end, we present as a contribution to the debate the idea of ​​an architectural sense that reveals itself as a gradual incorporation of various aspects of architectural practice into Hélio’s poetics.